2015
DOI: 10.1007/s00248-015-0646-z
|View full text |Cite
|
Sign up to set email alerts
|

One-Time Addition of Nano-TiO2 Triggers Short-Term Responses in Benthic Bacterial Communities in Artificial Streams

Abstract: Nano-TiO2 is an engineered nanomaterial whose production and use are increasing rapidly. Hence, aquatic habitats are at risk for nano-TiO2 contamination due to potential inputs from urban and suburban runoff and domestic wastewater. Nano-TiO2 has been shown to be toxic to a wide range of aquatic organisms, but little is known about the effects of nano-TiO2 on benthic microbial communities. This study used artificial stream mesocosms to assess the effects of a single addition of nano-TiO2 (P25 at a final concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…This study is a good model of the effects nano-TiO 2 could have on bacterial cells in wastewater. 125 Toxicity observations due to nanotitanium have been tested on live animals. Single low doses of nanoanatase TiO 2 particles in ICR mice's abdominal cavity, once a day for 14 days, have shown little differences in comparison to control mice.…”
mentioning
confidence: 99%
“…This study is a good model of the effects nano-TiO 2 could have on bacterial cells in wastewater. 125 Toxicity observations due to nanotitanium have been tested on live animals. Single low doses of nanoanatase TiO 2 particles in ICR mice's abdominal cavity, once a day for 14 days, have shown little differences in comparison to control mice.…”
mentioning
confidence: 99%
“…19 Another previous study reported a significant but temporary decrease in abundance of sediment bacteria in artificial streams in response to a single addition of a lower concentration of nano-TiO 2 (1 mg L −1 ). 28 The greater nano-TiO 2 resistance of the bacterial communities in the present study suggests that chronic addition of a low concentration of nano-TiO 2 may give the communities an opportunity to adapt to the stressor, such as through shifts in the relative abundance of sensitive and resistant taxa, whereas a single pulse addition of a high concentration of nano-TiO 2 does not provide the bacterial community with any opportunity to adapt. Results from our experiments support this hypothesis, as the chronic nano-TiO 2 additions resulted in shifts in bacterial community composition but no decrease in bacterial cell numbers at week 18, which corresponds to a total nano-TiO 2 load of 2.7 mg L −1 .…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, the one-time nano-TiO 2 addition of 1 mg L −1 in the previous study resulted in an almost immediate decrease in sediment bacterial numbers but no shift in the taxonomic composition of bacterial communities. 28 These results provide insight into the potential ecological effects of different nano-TiO 2 exposure scenarios, i.e. chronic low-level inputs from wastewater effluent versus single high concentration inputs from a spill, combined sewer overflow or infrastructure failure event.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation